Structure of WzxE the lipid III flippase for Enterobacterial Common Antigen polysaccharide - Audrey Le Bas; Bradley R. Clarke; Tanisha Teelucksingh; Micah Lee; Kamel El Omari; Andrew M. Giltrap; Stephen A. McMahon; Hui Liu; John H. Beale; Vitaliy Mykhaylyk; Ramona Duman; Neil G. Paterson; et al. (Open Biology)
The enterobacterial common antigen (ECA) is conserved in Gram-negative bacteria of the Enterobacterales order although its function is debated. ECA biogenesis depends on the Wzx/Wzy-dependent strategy whereby the newly synthesized lipid-linked repeat units, lipid III, are transferred across the inner membrane by the lipid III flippase WzxE. WzxE is part of the Wzx family and required in many glycan assembly systems, but an understanding of its molecular mechanism is hindered due to a lack of structural evidence. Here, we present the first X-ray structures of WzxE from Escherichia coli in complex with nanobodies. Both inward- and outward-facing conformations highlight two pairs of arginine residues that move in a reciprocal fashion, enabling flipping. One of the arginine pairs coordinated to a glutamate residue is essential for activity along with the C-terminal arginine rich tail located close to the entrance of the lumen. This work helps understand the translocation mechanism of the Wzx flippase family.